Enhancing clinical practice through action research: fostering a person-centred culture in healthcare - Rosted, Elizabeth; Christensen, Helle Gert; Lanther, Tina; McCormack, Brendan; Kjerholt, Mette (Frontiers in Health Services, 2025)
IntroductionDespite the growing recognition of person-centred practice in political declarations, strategic visions, and healthcare policies, a significant gap remains between the theoretical underpinnings of person-centred practice and its practical application in clinical settings. To bridge this gap, two departments at a university hospital in Denmark embarked on a collaborative initiative aimed at developing a person-centred culture and implementing a person-centred approach as the framework for nursing care.MethodAn action research study was undertaken from June 2020 to December 2023. To capture both the processes and outcomes of the study, data were collected through a combination of field studies, interviews and questionnaires. Data were analysed using thematic analysis.ResultsFive themes were generated from the data (1) We have learned a lot in relation to PCP; (2) The PCP framework is complex and difficult to understand and get hold of; (3) When implementing a person-centred framework, the overall context of the departments is important; (4) Psychological safety is important; (5) Values and Beliefs.ConclusionOverall, the study findings showed outcomes arising from the development of a caring culture towards one that is more person-centred. Both nurses and leaders’ competencies in relation to PCP were developed. The study resulted in increased awareness, knowledge and learning of PCP and during the study period new initiatives were initiated that contributed to the changes in and of clinical practice towards a more person-centred culture. During the study, blind spots like a disconnect between espoused values and experiences in clinical practice, as well as inappropriate workflows in the departments and the organization were uncovered.